String Instruments: Plucked - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers see and hear plucked string instruments from different parts of the world - - Hear musical styles of different cultures played on instruments as diverse as the guitar, lute, harp, balalaika, ukulele, and koto - - Discover some of the ways in which string instruments can be plucked, including some unusual contemporary techniques - - Join a banjo player as he demonstrates various playing techniques.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - For Students to Discover - - Student Follow-up - - Correlations with THE MUSIC CONNECTION - - Vocabulary - Music Contents - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Stringed instruments; Musical instruments; Films for the hearing impaired